What is effective classroom dialog? A comparative study of classroom dialog in Chinese expert and novice mathematics teachers’ classrooms - Zhao, Wenjun; Ma, Jing; Cao, Yiming (Frontiers in Psychology, 2022)
Conducting effective classroom dialogue is an important foundation for high-quality classrooms. This study investigates the characteristics of effective classroom dialogue from the perspective of Chinese mathematics classrooms. Classroom videotapes from 40 expert and 33 novice teachers were selected from a national project and analyzed through a developed coding framework. Results showed that the dominant types of dialogue in expert teachers’ classrooms were related to Basic Knowledge, Construction, Analysis, and Personal Information. Compared to novice teachers, expert teachers’ classrooms have a significantly lower proportion of dialogue on Basic Knowledge and significantly higher proportions of dialogue on Personal Information and Speculation. Based on expert teachers’ classrooms, the characteristics of effective classroom dialogue in the Chinese context were discussed. The analytical framework for classroom dialogue developed in this study could be a powerful tool for subsequent research. Suggestions are provided on increasing the effectiveness of classroom dialogue.